Privatization and Service Delivery in the Nigerian Power Sector: An Exposition on EEDC (West African Journal on Sustainable Development, 2024)
In the search for solutions to improve the performance of state-owned enterprises, several developing countries including Nigeria have embarked upon extensive privatization programmes within the framework of macroeconomic reform and liberation. Privatization of the power sector in Nigeria was premised on the fact that there were problems with the state owned power enterprises and privatization was part and parcel of a reform agenda to turn around these enterprises so that they can deliver electricity more efficiently and effectively. As revealed in the work, this kind of reasoning is ideologically loaded but cannot be substantiated by the existential reality of Nigeria. This paper hinges on Karl Marx’s theory of dialectical materialism in tandem with the structural functional theory focused on the effects of privatization with reference to the performance of EEDC in their service delivery functions. Using documentary sources of information and descriptive analysis, findings revealed among others that there has been little or no synergy between privatization and improvement in the level of power supply in Awka South Local Government. The nation still lacks the capacity to generate and transmit enough electricity to these distribution companies and the distribution companies in turn due to lack of technical expertise still record a lot of distribution losses. More disturbing is the exorbitant increase in the electrical bills and the continued menace of the arbitrary estimated billing system. The author recommends among others the need for more investors in the industry in order to level the competitive playing field and the recruitment of adequate manpower with the necessary technical knowledge.
Keywords: Privatization; Service delivery; Power sector; EEDC; Awka South